Research Data Integration in the Purdue Libraries. Issue 2 (1st February 2016) - Zilinski, Lisa D.; Barton, Amy; Zhang, Tao; Pouchard, Line; Pascuzzi, Pete
Abstract : EDITOR'S SUMMARY At the 2015 ASIS&T Research Data Access and Preservation (RDAP) Summit, panelists from Research Data @ Purdue University Libraries discussed the organizational structure intended to promote campus‐wide collaboration among diverse data specialists. Amy Barton explained her role as metadata specialist for research data and the importance of being engaged with evolving standards and best practices. As digital user experience specialist, Tao Zhang evaluated the Data Curation Profiles Toolkit, including an interview protocol librarians use to explore researchers' data needs and a web application for researchers to create data management plans. Line Pouchard, an information specialist focusing on big data, explored the data curation lifecycle model in general and its unique aspects in the context of big data. Information specialist for molecular biosciences, Pete Pascuzzi addressed the importance of bioinformatics for data reuse and having librarians work in an embedded position with researchers.